Optimization of CVD parameters for graphene synthesis through design of experiments. Issue 5 (15th December 2016) - Papon, Remi; Pierlot, Christel; Sharma, Subash; Shinde, Sachin Maruti; Kalita, Golap; Tanemura, Masaki
Abstract : The optimization process of the desired size and quality of graphene domains is usually very difficult due to the numerous interdependent parameters in chemical vapor deposition (CVD). Here, the method so‐called "designs of experiments" is applied to estimate the relative importance and value of some of these parameters and their interactions for the CVD growth of graphene on Cu foil using waste plastic as a solid source. We found that the growth temperature, time, rate of heating, and preannealing time of the substrate influence significantly graphene growth. In particular, the growth time and rate of increasing of the carbon source temperature appear as the main factors for the growth of graphene domains, where the manipulation of only these two parameters could dramatically change the size of crystals. Thus, our experiment shows that for synthesis of larger graphene domains using waste plastic not only do the growth parameters of Cu substrate influence graphene growth but also the carbon source rate of heating.